EXIGENCIAS DIDÁCTICAS PARA LA PRÁCTICA LABORAL POR GRUPOS DE CONTEXTOS LABORALES - Amelia Estévez Betancourt; Roberto Manuel Romero Bécares (University of Las Tunas, 2018)
La Educación Técnica y Profesional transita por las exigencias sociales de convertir a Cuba en un país que tenga como centro de la actividad económica el aumento de la producción y los servicios de forma sostenible. Por ello, es necesario potenciar la formación de obreros calificados y técnicos medios. Sin embargo, la dinámica de la práctica laboral que se realiza en la entidad productiva, carece de elementos didácticos que le permitan al alumno, integrar los contenidos para la solución de los problemas profesionales y mejorar su desempeño laboral. Por tal razón, en este artículo se realiza una propuesta de exigencias didácticas en función de la integración de contenidos laborales sistémicos contextuales, a partir de identificar el método proyecto como interobjeto que dinamiza la práctica laboral por grupos de contextos durante la formación de técnicos medios en la Educación Técnica y Profesional. ABSTRACT The Technical and Professional Education at the present time traffics for the social demands of transforming Cuba into a country that has like center of the economic activity the increase of the production and the services in a sustainable way. In this sense, it is demanded of a deep process of revision of what memorizes and he/she teaches, improving the formation of workers qualified and technician, on the base of the foundations of the Pedagogy of the Technical and Professional Education. However, the reach of the work dynamic practice which has a lack of elements from the didactic point of view which allows than the students may integrate knowledge in order to solve the problems and which that to improve the professional performance. For such a reason, in the article he/she is carried out a valuation of the didactic demands of the practical labor to integrate systemic and specifics contents, starting to identify the project methods like interobject, in the formation of workers and technical means in the Technical Education and Professional. All time that is interesting to know how it goes the process of teaching learning, in these practical laboured. KEY WORDS: Didactics, methods project, work practice, integration de contents.